Lifestyle Factors Aaffecting Gastro Esophageal Reflux Disease: A Cross-Sectional Study Among Healthy People in Qom-Iran - Khoobi M; Momenyan S; Salimi S; Sheikhhaeri MA; Farahabadi M; Barati A; Heidari S; Kazemi M (Zanjan University of Medical Sciences and Health Services, 2017)
Background: Gastroesophageal reflux disease (GERD) is one of the most common digestive system disorders. Life style factors may increase the risk of reflux disease. Objectives: We aimed to estimate prevalence of reflux and related life style factors among the population live in Qom. Methods: This is a cross-sectional study conducted among 1500 residents of Qom-Iran in 2014. Individuals were selected through a multi-stage sampling. They completed two questionnaires: FSSG questionnaire for diagnosis of GERD and a general questionnaire to measure demographic and lifestyle factors. Results: After data manipulation, 1130 individuals were analyzed in which 52/4% of them were female. Prevalence of GERD was 28%. The adjusted findings showed using PPIs (OR: 2.2, 95% CI: 2-5), taking H2RAs (OR: 4.7, 95% CI: 2.3-9. 4), the habit of quick eating (OR: 1.5, 95% CI: 1.1-2), extra salt consumption on daily meals (OR: 1.5, 95% CI: 1.05-2), lack of sleeping (OR: 2.6, 95% CI: 1.5-4.8), and consumption of white bread (OR: 1.7, 95% CI: 1.05-2.7) were related to increase the risk of GERD. Conclusion: Our findings showed lifestyle factors such as the habit of quick eating, extra salt on regular meals, lack of sleeping and using white bread were associated with increased risk of GERD. However, the habit of midnight snack, having dinner just before bedtime, lack of breakfast, smoking, drinking tea and coffee were not associated with increasing risk of GERD. It is recommended to carry out a cohort study among Iranians to evaluate the effect of life style risk factors on GERD.